Footmarks of Innate Immunity in the Ovary and Cytokeratin-Positive Cells as Potential Dendritic Cells - Spanel-Borowski, Katharina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The cyclic ovary can be seen as a site of tissue damage, repair and precisely controlled tissue homeostasis, as long ovulation and luteolysis can be compared with acute and chronic inflammation. Innate immunity appears to be a powerful force in the endocrine system, representing a novel concept. In this monograph, remarkable evidence is given for the immune-privileged ovary being an implant on the chicken chorioallantoic membrane with an areactive mesenchyme. Mild to severe tissue damages due to follicular atresia, follicular rupture, or intraovarian oocyte release do no lasting harm. The most exciting part relates to the analysis of cytokeratin-positive (CK+) cells, comparing the fate mapping of this cell type from the fetal ovary to the adult organ. Findings on toll-like receptor 4 regulation and interferon-gamma-dependent positive effects indicate that CK+ cells from human preovulatory follicles and bovine corpora lutea have similarities with nonlymphoid dendritic cells, a discovery that has the makings of a top story in basic and clinical research on the ovary.
1 Background -- 1.1 Innate Immunity, Toll-like Receptors (TLR), and Danger Signals 1.2 The Ovary, Tissue Remodelling, and Immune Privilege -- 1.3 Design -- 2 Material and Methods -- 2.1 Cyclic and Superovulated Ovaries from Rats, Hamsters, Rabbits as well as Canine, Bovine and Human Ovaries -- 2.1.1 Fibrinolytic Activity and Implants on the Chick Chorioallantois Membrane (CAM) -- 2.1.2 Fixation, Staining and Counting Ovarian Structures -- 2.2 Cell Culture Subtypes from Follicles Derived from Patients Under in Vitro Fertilization Therapy -- 2.3 Cell Culture Subtypes from Bovine Corpus Luteum (CL) and Characterization -- 3 Footmarks of Innate Immunity -- 3.1 The Complement System as Danger Sensor in General and in the Ovary -- 3.2 Mild Danger with Mild Response -- 3.2.1 Implantation of the Ovary into the CAM -- 3.2.2 Follicular Atresia -- 3.3 Moderate Danger by Preovulatory Follicle Rupture and Acute Inflammation with Eosinophils -- 3.3.1 Recruitment of Eosinophils and Substance P-Like Expression -- 3.4 Severe Danger in Superovulated Ovaries with Intra-Ovarian Oocyte Release and Thrombus Formation -- 4 Cytokeratin-Positive (CK+) cell as Potential Dendritic Cells -- 4.1 Dendritic cells, the TLR System in General and in the Ovary -- 4.2 Localisation of CK+ Cells in the Intact Ovary -- 4.2.1 Follicles in Foetal and Adult Ovaries -- 4.2.2 Corpus Luteum -- 5 Characterization of Isolated CK+ Cells -- 5.1 CK+ Cells from Preovulatory Follicles with TLR4 Expression -- 5.2 CK+ Cells from CL in Comparison to CK-Negative (CK-) Cells -- 5.2.1 Effects of Interferon-gamma on CK+ Cells from the CL Compared to CK- Cells and to Surface Epithelial Cells -- 5.2.2 Reflections on Quality of the CK+ Type 1 and Similarity with the Type 5 -- 6 Working Hypothesis and Challenges -- 7 Clinical Perspectives -- 8 Concluding Summary and Remarks -- References -- Subject index.
Keywords: Medicine; Human physiology; Immunology; Reproductive Medicine; Medicine & Public Health; Reproductive Medicine; Human Physiology; Immunology